The Analysis of Railway Vehicle with Semi-Active Secondary Suspension System under Harmonic Excitation Disturbance - HARUN, Mohd Hanif; W Abdullah, W. M. Zailimi; ABDULLAH, Mohd Azman; JAMALUDDIN, Hishamuddin; ABD RAHMAN, Roslan; HUDHA, Khisbullah (2013)
– Railway vehicle dynamic industry is growing rapidly by the improvement of traditional suspension system to the advanced control technology. By increasing the speed of the vehicle, the uncomfortable of the passengers are also increase. This paper concentrates on the semi-active suspension control applied to the secondary suspension system of railway vehicle. The governing equations of 3-DOF half model with semi-active damper were formulated which includes a vehicle body, bogie and two wheel-sets. The responses of railway vehicle body integrated with semi-active damper control are evaluated under sinusoidal track irregularity. The suspension performance criteria of semi-active damper are compared with the passive suspension system in the time domains, which use a passive viscous damper. From the simulation results, it can be seen that the semi-active damper is able to attenuate unwanted body motion occurred by track irregularity compared to the passive system.